"Give me Liberty or Give me Covid-19": Anti-lockdown protesters were never Trump puppets. Issue 3 (September 2020) - Schradie, Jen
Dismissing conservative participants in protests as duped fools or ranting ideologues who have fallen prey to fake news is a dangerous reaction that fails to recognize the essential and grassroots role they play in profoundly effective conservative messaging that continues to outfox progressive information campaigns. This article uses the collective action against Covid-19 stay-at-home orders and mask requirements as an example of the broader arguments in the book, The Revolution That Wasn't: How Digital Activism Favors Conservatives (Harvard University Press, 2019).